2006
DOI: 10.3349/ymj.2006.47.4.480
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Inducible Clindamycin Resistance in Staphylococcal Isolates at a Korean Tertiary Care Hospital

Abstract: Clindamycin resistance in Staphylococcus species can be either constitutive or inducible. Inducible resistance cannot be detected by the conventional antimicrobial susceptibility test. In this study, we determined the prevalence of inducible clindamycin resistance in staphylococcal isolates at a Korean tertiary care hospital. Between February and September 2004, 1,519 isolates of Staphylococcus aureus and 1,043 isolates of coagulase-negative staphylococci (CNS) were tested for inducible resistance by the D-zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
2
19
2
1
Order By: Relevance
“…The percentage of cMLS resistance (47%; 130/274) in the present study was similar to that found in an earlier study in southern Taiwan from 1995 to 2006 (52%; 77/149) (4) but much higher than in several other countries, such as Japan (10%; 48/478) (30), southeastern Turkey (8%; 1/13) (31), and Korea (20%; 40/205) (32). The iMLS phenotype was detected in 36% (98/274) of erythromycin-resistant MSSA isolates, which equals 68% (98/144) of erythromycin-resistant, clindamycin-susceptible strains, slightly lower than in a previous report from southern Taiwan (76%; 55/ 72) (4) or in Japan (93%; 397/428) (30) but higher than in Korea (35%; 58/165) (32) or in the United States (60%; 73/122) (33).…”
Section: Discussionsupporting
confidence: 78%
“…The percentage of cMLS resistance (47%; 130/274) in the present study was similar to that found in an earlier study in southern Taiwan from 1995 to 2006 (52%; 77/149) (4) but much higher than in several other countries, such as Japan (10%; 48/478) (30), southeastern Turkey (8%; 1/13) (31), and Korea (20%; 40/205) (32). The iMLS phenotype was detected in 36% (98/274) of erythromycin-resistant MSSA isolates, which equals 68% (98/144) of erythromycin-resistant, clindamycin-susceptible strains, slightly lower than in a previous report from southern Taiwan (76%; 55/ 72) (4) or in Japan (93%; 397/428) (30) but higher than in Korea (35%; 58/165) (32) or in the United States (60%; 73/122) (33).…”
Section: Discussionsupporting
confidence: 78%
“…The interpretation of this result is difficult; previous reports showed no apparent differences regarding the incidence of inducible resistance for erythromycin and clindamycin-susceptible MSSA and MRSA strains [12]. We postulate that this might be due to area-specific prevalence of each particular clone.…”
Section: Discussionmentioning
confidence: 76%
“…This is where the D-test becomes significant. [15][16][17] Lim et al, [18] reported inducible resistance in 9.6% CoNS isolates by the disc diffusion test whereas Schmitz et al, [19] documented a fairly high …”
Section: Discussionmentioning
confidence: 99%